Compound Optical Film Using Gray Scale Mask Embedded with Microvoids. (28th November 2012) - Pan, C. T.; Chen, Y. C.; Chen, Y. J.; Wang, W. C.; Yang, H. C.; Wu, H. C.
Abstract : This study presents a compound optical film to improve luminance and uniformity to apply in side-LED (light-emitting diode) backlight module. LIGA (lithographie galvanoformung abformung) technology, soft lithography, and homemade gray scale mask were combined to fabricate microlens array. Optical film with variable size microlens array embedded with microvoids was designed and manufactured. FRED software was used to simulate optical performance. Microvoids were quantitatively embedded in the PDMS (polydimethylsiloxane) optical film. Under the quantitative control of air pressure, those microvoids inside the optical film can cause light diffusion. The compound optical film with embedded microvoids, multiaspect ratio, and variable size microlens array can be fabricated quickly without substrate. Luminance colorimeter BM-7A from TOPCON was used to carry out the optical measurement. According to the measured data, the compound optical film with embedded microvoids can enhance the luminance up to 5% and the uniformity up to 6.5%   ~   8.4%. The optical efficiency can be improved via the compound optical film.